The Effect of Principal's Transformational Leadership and Job Satisfaction on the Performance of State Elementary School Teachers - Dwi Sartika Sari; Rohana Rohana; Yasir Arafat (Journal of Social Work and Science Education, 2026)
This study analyzes the influence of principal's transformational leadership and job satisfaction on teacher performance at public elementary schools in Sematang Borang District, Indonesia. Employing a quantitative approach, the research targeted a population of 101 teachers, all of whom were selected as samples using saturated sampling technique. Data were collected through Likert-scale questionnaires and documentation, then analyzed using regression tests, t-tests, and F-tests. The results reveal three key findings: first, principal's transformational leadership has a positive and significant influence on teacher performance; second, job satisfaction also demonstrates a positive and significant influence on teacher performance; and third, both variables simultaneously exert a positive and significant influence on teacher performance. The study concludes that improving teacher performance requires strengthening both transformational leadership practices and job satisfaction levels concurrently. The novelty lies in examining the combined effects of these two variables within the underexplored context of elementary schools in Sematang Borang District, providing localized empirical evidence. Practically, school principals should adopt transformational behaviors such as intellectual stimulation and individualized consideration while also systematically addressing teacher job satisfaction through recognition, supportive working conditions, and professional growth opportunities. This study contributes to educational leadership literature by confirming that transformational leadership and job satisfaction are not mutually exclusive but rather complementary drivers of teacher performance, suggesting that holistic interventions targeting both leadership style and teacher welfare yield optimal results in elementary school settings.